The role of parents in children's education in beneficiary families of the Family Hope Program - Septiani, Riska; Brata, Nugroho Trisnu; Hardati, Puji (Universitas Negeri Semarang, 2022)
The good and bad of the nation's generation are determined by the personal formation of their respective families. Most families who are beneficiaries of the Jaya Mulia Village Family Hope Program have a background as laborers, so families have to work hard to meet basic needs and neglect their children's education. This study aims to determine the role and constraints faced in children's education and the benefits of the “Program Keluarga Harapan” assistance in the education component. The research uses qualitative methods and data collection techniques through observation, interviews and documentation. The results showed four kinds of parental roles: modeling, mentoring, organizing, and teaching. However, not all parents carry out their role because there are several obstacles such as limited time, education level, and the social environment's influence. One of the efforts made by the government to improve the quality of education is through PKH. PKH not only assists in the form of cash but also provides training, guidance and motivation to parents in providing better care, protection and education for their children. This research is expected to contribute ideas to the community that parents have greater responsibilities.